Mold system, device and method for preparing metal core piezoelectric fibers
By combining a conical mold system with a LiCl inducer, the problems of coating uniformity and weak adhesion in the preparation of metal-core piezoelectric fibers were solved, realizing the preparation of high-performance, low-cost metal-core piezoelectric fibers suitable for flexible sensors and structural health monitoring.
Patent Information
- Application Number
- CN202511704693.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-20
- Publication Date
- 2026-01-23
AI Technical Summary
Existing technologies struggle to produce metal-core piezoelectric fibers with good uniformity and consistency. The bonding force between the piezoelectric layer and the metal core is weak, and the process is complex and difficult to achieve continuous production.
By employing a conical mold system and an elastic suspension centering system, combined with LiCl inducer and coagulation bath crystallization process, and through mold structure design and process optimization, uniform coating of piezoelectric layer and high β phase content are achieved, enhancing interfacial bonding and simplifying the production process.
It significantly improves the performance uniformity and consistency of piezoelectric fibers, enhances the interfacial bonding between the piezoelectric layer and the metal core, simplifies the manufacturing process and reduces costs, and is suitable for high-performance flexible sensors, energy harvesters and structural health monitoring.
Smart Images

Figure CN121398441A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of piezoelectric materials technology, and in particular to mold systems, apparatus and methods for preparing metal-core piezoelectric fibers, applicable to fields such as high-performance flexible sensors, energy harvesters and structural health monitoring. Background Technology
[0002] Piezoelectric fibers are key smart materials capable of converting mechanical energy into electrical energy, and they have broad application prospects in flexible sensors, energy harvesters, structural health monitoring, and wearable electronic devices. Metal-core piezoelectric fibers, in particular, use highly conductive metal wires as inner electrodes and a supporting substrate, wrapped with a piezoelectric material layer to form a coaxial cable-like structure. This design not only facilitates charge collection and transport but also combines the flexibility and strength of a metal core, providing an ideal solution for fabricating high-performance integrated smart fiber sensors.
[0003] Currently, the main methods for preparing metal-core piezoelectric fibers include electrospinning, melt coating, and conventional solution coating. However, these traditional methods all have significant technical bottlenecks that limit the performance and reliability of the final product. (1) Challenges in coating uniformity and coaxiality control: Piezoelectric layers prepared by electrospinning are usually porous nonwoven fabrics with poor density and uneven fiber diameters, resulting in low consistency of piezoelectric response. Melt coating and conventional solution coating methods are difficult to control the concentricity of the coating precisely, and the metal core is prone to displacement during the coating process, causing uneven thickness of the piezoelectric layer. Such inhomogeneity will directly cause differences in piezoelectric properties in different sections of the fiber, forming a sensing "blind zone" and seriously affecting its application in the field of precision sensing.
[0004] (2) Insufficient piezoelectric phase (β phase) content: The piezoelectric properties of polyvinylidene fluoride (PVDF) and its copolymer P(VDF-TrFE) mainly originate from the β-phase with high dipole moment in the molecular chain. Although electrospinning can induce β-phase generation through stretching flow field, the process stability is poor; while solution coating usually lacks effective in-situ polarization methods, resulting in insufficient β-phase content in the fiber, requiring subsequent high electric field polarization treatment. This not only increases the complexity and energy consumption of the process, but also brings the risk of breakdown.
[0005] (3) Weak bonding between the piezoelectric layer and the metal core: If the bonding between the piezoelectric layer and the metal core substrate is poor, it is easy for the interface to peel off or the coating to fall off when subjected to cyclic stress or complex working conditions for a long time, which will lead to signal attenuation or even functional failure. Existing methods have limited ability to promote tight bonding at the interface, which restricts the mechanical durability and service life of fiber devices.
[0006] (4) The process is complex and the repeatability is poor: For example, although methods such as template melting and impregnation can obtain specific structures, they generally have problems such as lengthy process flow and strict parameter control, making it difficult to achieve continuous large-scale production, resulting in the inability to guarantee the repeatability of preparation and product consistency.
[0007] Therefore, there is an urgent need for a new preparation method that can simultaneously overcome several key challenges such as coating uniformity, high β phase content, strong interfacial bonding, and process simplicity, so as to promote the metal core piezoelectric fiber from the laboratory to practical engineering applications. Summary of the Invention
[0008] In view of this, in order to overcome the above-mentioned defects of traditional metal-core piezoelectric fibers, the present invention provides a mold system, device and method for preparing metal-core piezoelectric fibers. Through mold structure innovation and synergistic optimization of formulation and process, the efficient preparation of high-performance metal-core piezoelectric fibers is achieved, significantly improving the performance uniformity and consistency of piezoelectric fibers, obtaining excellent piezoelectric properties and durability, enhancing the interfacial bonding force between the piezoelectric layer and the metal core, simplifying the production process and reducing costs.
[0009] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a mold system for the fabrication of metal-core piezoelectric fibers, comprising: A conical mold with a through conical inner hole for the metal core substrate to pass through and be coated with a piezoelectric material solution; The elastic suspension centering system is connected at one end to the conical mold and at the other end to the fixing device, giving the mold a preset angular degree of freedom to achieve dynamic centering of the metal core substrate.
[0010] Preferably, the preset angle is ±3°.
[0011] Preferably, the elastic suspension centering system adjusts the tension of the elastic fiber rope to generate torque when the conical mold shifts on the metal core base, driving the mold to rotate to restore centering.
[0012] In a second aspect, the present invention provides an apparatus for preparing metal-core piezoelectric fibers, comprising the aforementioned mold system, and: A metal core conveying mechanism for conveying a metal core substrate through the conical inner hole; A solution supply mechanism for injecting a piezoelectric material solution into the conical inner hole; A coagulation bath mechanism, located downstream of the mold system, is used to receive the coated metal core substrate and perform crystallization treatment.
[0013] Thirdly, the present invention also provides a method for preparing metal-core piezoelectric fibers based on the above-described apparatus for preparing metal-core piezoelectric fibers, comprising the following steps: Step (1) Metal core substrate pretreatment: Select pure metal wire as substrate, clean and dry it for later use; Step (2), Preparation of mixed solution: Dissolve P(VDF-TrFE) polymer and β phase inducer in organic solvent to form a homogeneous P(VDF-TrFE) / β phase inducer mixed solution; Step (3), mold-assisted coating: the metal core substrate is conveyed through the conical inner hole by the metal core conveying mechanism, and the solution supply mechanism injects the P(VDF-TrFE) / β phase inducer mixed solution obtained in step (2) into the conical inner hole to coat the surface of the metal core substrate. During the coating process, the centering is adjusted in real time by the torque generated by the radial pressure, and the shear force generated by the conical structure is used to induce the orientation of the P(VDF-TrFE) molecular chain. Step (4), solidification bath crystallization: The coated metal core substrate is immersed in the solidification bath mechanism, and P(VDF-TrFE) crystallizes to form a dense piezoelectric layer through dynamic phase separation; Step (5), Drying and post-treatment: Remove the residual organic solvent in the piezoelectric layer, dry it and then prepare the outer electrode and encapsulate it to obtain the metal core piezoelectric fiber.
[0014] Preferably, in step (2), the molar ratio of VDF to TrFE in the P(VDF-TrFE) polymer is 80:20.
[0015] Preferably, in step (2), the β-phase inducer is LiCl.
[0016] Preferably, in step (2), the mass fraction of P(VDF-TrFE) polymer is 12~18wt% and the mass fraction of β phase inducer is 5~9wt%.
[0017] Preferably, in step (4), the crystallization temperature of the coagulation bath is 25°C.
[0018] Preferably, in step (5), after drying, conductive copper paint is sprayed onto the surface of the piezoelectric layer using an air spraying method to form an outer electrode layer, thereby constructing an integrated coaxial structure of "metal-piezoelectric layer-electrode-encapsulation" with a metal core as the inner electrode, conductive copper paint as the outer electrode, and an outer layer encapsulated by EPDM heat shrink tubing.
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) Significantly improved the uniformity and consistency of piezoelectric fiber performance: Thanks to the automatic alignment mechanism of the mold, the prepared piezoelectric fiber piezoelectric layer has uniform thickness and high coaxiality. Test results show that within a length range of 200mm, the maximum deviation of the output voltage is ≤0.11V, thus achieving uniformity of full-area sensing and effectively eliminating monitoring blind spots.
[0020] (2) Excellent piezoelectric properties and durability were achieved: Through the synergistic effect of LiCl induction and mold shear orientation, the piezoelectric layer has a high β phase content and a dense microstructure. The final product not only has a high initial piezoelectric output voltage (about 1.4V@10N), but also has excellent fatigue resistance (signal attenuation of only 2.8% after 500 cycles), thus meeting the requirements of long-term and stable dynamic sensing.
[0021] (3) Enhanced interfacial bonding between the piezoelectric layer and the metal core: Optimized pretreatment, coating and crystallization processes enable a strong bond between the piezoelectric layer and the metal core substrate, with a peel force test of ≥5N, thereby eliminating the technical problem of easy coating peeling and significantly extending the product's service life.
[0022] (4) The production process is simplified and the cost is reduced: The wet process adopted in this invention does not require expensive equipment, realizes continuous preparation, and eliminates the traditional and energy-consuming subsequent polarization process through solution-induced crystallization, thereby making the entire process simpler and more efficient, which is conducive to large-scale production and has significant industrial application value. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of a mold-aided coating equipment. The left side shows the overall structure, and the right side shows an enlarged view of the conical mold. Figure 2 A schematic diagram of the continuous fabrication process of metal-core piezoelectric fibers; Figure 3 This is a schematic diagram of automatic centering and shearing orientation of a conical mold and a metal core. The left side shows the automatic centering schematic diagram, and the right side shows the shearing orientation schematic diagram. Figure 4 This is a schematic diagram of the formation process of the cross-sectional structure of a metal-core piezoelectric fiber. Figure 5 Photograph of a metal-core piezoelectric fiber (MPF); Figure 6 The diagram shows the force-sensitive characteristics test of metal core piezoelectric fiber. The left side is a schematic diagram of the test structure, and the right side (1) shows the output voltage distribution of the global sensing uniformity test in Example 1, and (2) shows the piezoelectric output voltage change curve of the cyclic fatigue test in Example 1. Figure 7The crystallization of the piezoelectric layer on the surface of the metal core under different mass fractions are shown. Among them, (1) is the crystallization of the piezoelectric layer on the surface of the metal core in Example 2, (2) is the crystallization of the piezoelectric layer on the surface of the metal core in Example 3, (3) is the crystallization of the piezoelectric layer on the surface of the metal core in Example 1, and (4) is the crystallization of the piezoelectric layer on the surface of the metal core in Example 4. Figure 8 The image shows a comparison of the β-phase content of the piezoelectric layer with and without the addition of an inducing agent. The left side shows the crystal phase distribution of the sample without LICL and the sample with 7% LICL, obtained by XRD scanning. The right side shows the β-phase content of the two samples calculated according to Beer-Lambert's law.
[0024] Figure 9 The output voltage comparison curves of piezoelectric layers with and without added inducing agents are shown. The left side is the output voltage comparison curve of the piezoelectric layer without LICL inducing agent (Example 5), and the right side is the output voltage comparison curve of the piezoelectric layer with LICL inducing agent (Example 1). Figure 10 The piezoelectric layer β phase content and piezoelectric output voltage curves with 5wt% and 7wt% inducer added in Example 6 are compared. The left side shows the β phase content, and the right side shows the piezoelectric output voltage curves. Figure 11 The piezoelectric layer β phase content and piezoelectric output voltage curves with 7wt% and 9wt% inducer added in Example 7 are compared. The left side shows the β phase content, and the right side shows the piezoelectric output voltage curves.
[0025] In the diagram, 1. Winder; 2. Roller; 3. Rotating platform; 4. Elastic suspension centering system; 5. Conical mold; 6. Fixing device; 7. Solution supply mechanism; 8. Metal core; 9. Coagulation bath mechanism; 10. Thermosetting; 11. Winding; 12. Polyvinylidene fluoride-trifluoroethylene copolymer solution; 13. Polyvinylidene fluoride-trifluoroethylene crystal; 14. Metal core piezoelectric layer; 15. Metal core piezoelectric fiber; 16. Pressure test probe; 17. Piezoelectric signal data acquisition card; 18. Weight; 19. Fixing platform. Detailed Implementation
[0026] like Figure 1 As shown, the present invention provides a mold system for fabricating metal-core piezoelectric fibers 15, comprising: The conical mold 5 has a through conical inner hole for the metal core 8 substrate to pass through and be coated with the piezoelectric material solution. The conical mold 5 is preferably fabricated using 3D printing, and its material is preferably solvent-resistant and high-temperature resistant polytetrafluoroethylene (PTFE). The diameter of the conical inner hole is preferably 0.6 mm, matching the 400 μm metal core 8 (preferably copper wire) to ensure uniform coating thickness.
[0027] The elastic suspension alignment system 4 is connected at one end to the conical mold 5 and at the other end to the fixing device 6, giving the mold a preset angular degree of freedom to achieve dynamic alignment of the metal core 8 base. The preset angle is preferably ±3°. The elastic suspension alignment system 4 adjusts the tension of the elastic fiber ropes to generate torque in the conical mold 5 when the metal core 8 base shifts, driving the mold to rotate and restore alignment. Preferably, the mold is elastically suspended below the equipment by four highly elastic fiber ropes. The tension and length of the elastic fiber ropes are adjustable, giving the mold a ±3° angular degree of freedom to achieve automatic alignment of the metal core 8.
[0028] The present invention also provides an apparatus for preparing a metal-core piezoelectric fiber 15, comprising the above-described mold system, and: A metal core 8 conveying mechanism is used to convey the metal core 8 substrate through the conical inner hole. Preferably, the metal core 8 is a 400μm copper wire adapted to the conical inner hole with a diameter of 0.6mm to ensure uniform coating thickness. Figure 1 As shown, the metal core 8 conveying mechanism preferably uses a winder 1, rollers 2, and a rotating platform 3.
[0029] Winder 1: Located at the beginning of the equipment, it is used to receive the metal core 8 substrate (such as 400μm copper wire) to be processed. The metal core 8 is released from the winder 1 and enters the conveying path of the subsequent rollers 2 and the rotating platform 3. The winder 1 achieves continuous unwinding of the metal core 8 through rotation, providing a stable supply of raw materials for the entire conveying process.
[0030] Rollers 2: Multiple sets are arranged at intervals along the conveying path of the metal core 8, including guide rollers 2 and support rollers 2. After the metal core 8 is released from the winder 1, it passes through the grooves of each roller 2 in sequence, forming a "multi-wheel guide and support" conveying link. The guide rollers 2 correct the conveying direction of the metal core 8, ensuring that it is aligned with the conical inner hole; the support rollers 2 support the metal core 8, preventing it from sagging off the path due to its own weight, thus jointly ensuring the straightness and stability of the conveying.
[0031] Rotating platform 3: Located downstream of the equipment. After passing through roller 2, the metal core 8 needs to be collected by adjusting its posture on the rotating platform 3. This platform can rotate around a horizontal axis to adjust the spatial posture of the metal core 8, allowing the metal core 8 to be continuously wound around the rotating platform 3.
[0032] The winder 1 enables continuous feeding, the roller group 2 ensures conveying stability, and the rotating platform 3 enables continuous collection. The three work together to ensure continuous and precise delivery of the metal core 8, providing key support for the preparation of metal core piezoelectric fibers 15 with excellent uniformity.
[0033] Solution supply mechanism 7 is used to inject piezoelectric material solution into the conical inner hole. For example, a syringe is used to inject the piezoelectric material solution into the actuating mold.
[0034] The solidification bath mechanism 9 is located downstream of the mold system and is used to receive the coated metal core 8 substrate and perform crystallization treatment.
[0035] like Figure 2-4 As shown, based on the above-described apparatus for preparing metal-core piezoelectric fibers 15, the present invention provides a method for preparing metal-core piezoelectric fibers 15, comprising the following steps: Step (1) Pretreatment of the metal core 8 substrate: Select pure metal wire as the substrate, and clean and dry it for later use.
[0036] Step (2), Preparation of the mixed solution: The P(VDF-TrFE) polymer and the β-phase inducer are dissolved in an organic solvent to form a homogeneous P(VDF-TrFE) / β-phase inducer mixed solution. In the P(VDF-TrFE) polymer, the molar ratio of VDF to TrFE is 80:20. The β-phase inducer is preferably LiCl. The mass fraction of the P(VDF-TrFE) polymer is preferably 12-18 wt%, more preferably 16 wt%; the mass fraction of the β-phase inducer is preferably 5-9 wt%, more preferably 7 wt%.
[0037] Step (3), mold-assisted coating: The metal core 8 substrate is conveyed through the conical inner hole by the metal core 8 conveying mechanism. The solution supply mechanism 7 injects the P(VDF-TrFE) / β phase inducer mixed solution obtained in step (2) into the conical inner hole to coat the surface of the metal core 8 substrate. During the coating process, the centering is adjusted in real time by the torque generated by the radial pressure. At the same time, the shear force generated by the conical structure induces the orientation of the P(VDF-TrFE) molecular chain.
[0038] Step (4), coagulation bath crystallization: The coated metal core 8 substrate is immersed in the coagulation bath mechanism 9, and P(VDF-TrFE) crystallizes to form a dense piezoelectric layer through dynamic phase separation. In this step (4), the coagulation bath crystallization temperature is preferably 25℃. When the temperature is too low, a porous structure is easily formed, and when the temperature is too high, the crystallization rate is too slow, which easily leads to a decrease in coating adhesion. At a temperature of 25℃, the solvent diffusion and crystallization rate reach equilibrium, and the β-phase induction effect, piezoelectric performance and cycle stability are optimal.
[0039] Step (5), Drying and Post-treatment: Remove the residual organic solvent in the piezoelectric layer, dry it, and then prepare the outer electrode and encapsulate it to obtain the metal core piezoelectric fiber 15. In this step (5), after drying, conductive copper paint is sprayed onto the surface of the piezoelectric layer using an air spraying method to form an outer electrode layer, thus constructing an integrated coaxial structure of "metal-piezoelectric layer-electrode-encapsulation" with the metal core 8 as the inner electrode, the sprayed conductive copper paint as the outer electrode, and the outer layer encapsulated by EPDM heat shrink tubing.
[0040] By way of example, the present invention provides a preferred method for preparing the above-mentioned metal core piezoelectric fiber 15, the specific process of which is as follows: Step 1: Fabrication of the metal core 8-substrate Commercially available pure copper wire with a diameter of 400 μm (surface roughness Ra≤0.8 μm, ensuring tight bonding of the subsequent piezoelectric layer) was selected as the substrate for the metal core 8. The wire was ultrasonically cleaned with anhydrous ethanol for 10–15 minutes to remove surface oil, and then dried in an 80℃ oven for 30 minutes for later use.
[0041] Step 2: Preparation of P(VDF-TrFE) / LiCl mixed solution 2.1 Raw material preparation: Vinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE), with a molar ratio of vinylidene fluoride (VDF) to trifluoroethylene (TrFE) of 80:20), lithium chloride (LiCl, β-phase inducer) and N,N-dimethylformamide (DMF) solvent were selected.
[0042] 2.2 Pretreatment: Place P(VDF-TrFE) powder in a vacuum drying oven at 180℃ and dry for 10 hours to thoroughly remove moisture and residual impurities, and avoid generating bubbles in the subsequent solution.
[0043] 2.3 Dissolving LiCl: Add LiCl powder to DMF and stir at 60℃ and 300 rpm for 1 hour until LiCl is completely dissolved to form a homogeneous LiCl / DMF solution.
[0044] 2.4 Mixing preparation: The pretreated P(VDF-TrFE) powder was added to the above LiCl / DMF solution, and the mass fraction of P(VDF-TrFE) was controlled at 16 wt% and the mass fraction of LiCl was controlled at 7 wt%. The mixture was stirred continuously at 60℃ and 500 rpm for 1 hour to form a homogeneous P(VDF-TrFE) / LiCl mixed solution without precipitation.
[0045] Step 3: Mold system-assisted coating 3.1 Mold System Assembly: A conical mold 5 made of polytetrafluoroethylene (PTFE) with both solvent resistance and high-temperature resistance is fabricated using 3D printing technology. The conical inner diameter of the mold 5 is 0.6 mm, matching the 400 μm copper wire to ensure uniform coating thickness. The mold is elastically suspended below the equipment by four highly elastic fiber ropes. The length of the fiber ropes is adjustable, giving the mold ±3° of angular freedom, enabling automatic centering of the metal core 8 (e.g., ...). Figure 3 (As shown).
[0046] 3.2 Positioning of the metal core 8: Tension the copper wire prepared in step 1 between the upper and lower pulleys along the axis of the mold, and adjust the height of the pulleys to make the center of the copper wire precisely aligned with the center of the inner hole of the mold.
[0047] 3.3 Solution Injection and Coating: The mixed solution prepared in step 2 is injected into the mold at a rate of 0.5–1 mL / min using a syringe, while the copper wire is controlled to move downwards along the axis at a rate of 40 mm / s. The conical structure of the mold generates an axial scraping force F and a radial pressure Q: the axial force precisely controls the coating thickness, and the radial force induces the directional alignment of P(VDF-TrFE) molecular chains through shear orientation, initially promoting the formation of the β phase; when the copper wire deviates, the radial pressure Q generates a torque τ = Q・ΔR (ΔR is the deviation amount), driving the mold to rotate in real time to restore centering and ensure the coaxiality of the coating (e.g., ...). Figure 2 –3 (as shown in Figure 3).
[0048] Step 4: Crystallization in the coagulation bath Immediately immerse the copper wire coated in step 3 into a 25°C pure water coagulation bath, controlling the residence time to be 30–60 seconds. After the high-temperature (60°C) P(VDF-TrFE) / LiCl solution comes into contact with the low-temperature pure water, the solvent DMF rapidly diffuses into the water, and at the same time, the solution temperature drops sharply, causing P(VDF-TrFE) to instantly reach a supersaturated state. Rapid crystallization is achieved through dynamic phase separation, forming a dense and uniform P(VDF-TrFE) piezoelectric layer on the surface of the copper wire. The coagulation bath temperature is strictly controlled at 25°C. If the temperature is too low, a porous structure will easily form, damaging the piezoelectric performance. If the temperature is too high, the crystallization rate will be slow and the coating will easily fall off. The pure water is replaced every 2 hours to avoid DMF accumulation affecting the crystallization effect.
[0049] Step 5: Drying to remove solvent The fibers from step 4 are removed using winding 11. The fibers are first blown dry with compressed air at a pressure of 0.1–0.2 MPa (to avoid damaging the piezoelectric layer) to remove surface moisture, then placed in an 80℃ hot air drying oven for 30 minutes; or dried in a ventilated environment at 25±2℃ and 40%–60% relative humidity for 12 hours, followed by thermosetting 10 to completely remove residual DMF solvent from the piezoelectric layer, obtaining a composite structure with a metal core piezoelectric layer 14. Figure 4 As shown: The surface of the metal core 8 is coated with a polyvinylidene fluoride-trifluoroethylene copolymer solution 12, which crystallizes in a coagulation bath to form polyvinylidene fluoride-trifluoroethylene crystals 13. After drying, a metal core piezoelectric layer 14 is obtained. The thickness of the metal core piezoelectric layer 14 is controlled to be 100–120 μm. At this thickness, the bonding force between the metal core piezoelectric layer 14 and the copper wire is optimal, and the peel force test value is ≥5 N.
[0050] Step 6: External Electrode Fabrication and Packaging 6.1 External Electrode Coating: Environmentally friendly conductive copper paint (Copprint Co., Ltd., Kyoto, Japan) was selected and sprayed onto the surface of the composite structure using an air spraying method. The spraying pressure was 0.3 MPa, the spraying distance was 15–20 cm, and the spraying was repeated 2–3 times. After each spraying, the coating was dried at 60℃ for 10 minutes to form an external electrode layer with a thickness of 5–10 μm (conductivity ≥5×10⁵ S / m as tested by the four-probe method). The metal core 8 serves as the internal electrode, forming a double-layer electrode structure with the external electrode to achieve efficient extraction of piezoelectric charge.
[0051] 6.2 Encapsulation: The fiber coated with the external electrode is inserted into an EPDM heat shrink tubing (inner diameter matching the fiber's outer diameter). Heating with an 80℃ hot air gun for 5 minutes ensures the heat shrink tubing tightly wraps the fiber, significantly improving its abrasion resistance and anti-interference ability. This ultimately yields a metal-core piezoelectric fiber 15 (MPF), as shown in the image. Figure 5 As shown.
[0052] The inventive principle of this invention is as follows: (1) Mold structure innovation: The conical mold 5 with ±3° angular freedom is designed through the elastic suspension system. It not only uses axial scraping force to accurately control the coating thickness, but also induces the directional arrangement of P(VDF-TrFE) molecular chains through radial pressure shear orientation, which initially promotes the formation of piezoelectric β phase in the coating stage.
[0053] (2) Synergistic innovation of formulation and process: 7 wt% LiCl was introduced into the solution as a β phase inducer and the coagulation bath crystallization process (25℃) was optimized. Through synergistic effect, the β phase crystallization content of P(VDF-TrFE) was greatly increased during the dynamic phase separation process, eliminating the high electric field polarization step, simplifying the process and enhancing the piezoelectric performance.
[0054] (3) Integrated process innovation: The key steps such as mold-assisted coating, shear-induced orientation, solution-induced crystallization and thermal phase separation are integrated into a continuous and efficient process to achieve seamless connection from metal core 8 to finished fiber, ensuring product performance consistency and repeatability.
[0055] (4) Innovative structural design: Construct an integrated coaxial structure of “metal core 8 (inner electrode) - piezoelectric layer - outer electrode (conductive copper paint) - encapsulation (EPDM heat shrink tubing)” to significantly optimize charge extraction efficiency, while improving the mechanical wear resistance, environmental interference resistance and long-term working stability of the fiber.
[0056] The technical solution of the present invention will be clearly and thoroughly described below with reference to specific embodiments.
[0057] Example 1 Step 1: Fabrication of the metal core 8-substrate Commercially available pure copper wire with a diameter of 400 μm was selected as the metal core substrate, with a surface roughness Ra ≤ 0.8 μm to ensure tight bonding of the subsequent piezoelectric layer. The surface was ultrasonically cleaned with anhydrous ethanol for 10 minutes to remove oil, and then dried in an 80℃ oven for 30 minutes for later use.
[0058] Step 2: Preparation of P(VDF-TrFE) / LiCl mixed solution 2.1 Raw material preparation: Vinylidene fluoride-trifluoroethylene copolymer (P(VDF-TrFE), with a molar ratio of vinylidene fluoride (VDF) to trifluoroethylene (TrFE) of 80:20), lithium chloride (LiCl, β-phase inducer) and N,N-dimethylformamide (DMF) solvent were selected.
[0059] 2.2 Pretreatment: Place P(VDF-TrFE) powder in a vacuum drying oven at 180℃ and dry for 10 hours to thoroughly remove moisture and residual impurities, and avoid generating bubbles in the subsequent solution.
[0060] 2.3 Dissolving LiCl: Add LiCl powder to DMF and stir at 60℃ and 300 rpm for 1 hour until LiCl is completely dissolved to form a homogeneous LiCl / DMF solution.
[0061] 2.4 Mixing Preparation: The pretreated P(VDF-TrFE) powder was added to the above LiCl / DMF solution, controlling the mass fraction of P(VDF-TrFE) to be 16 wt% (e.g., ...). Figure 7 As shown in (3), the mass fraction of LiCl was 7 wt%. The mixture was stirred continuously at 60℃ and 500 rpm for 1 hour to form a homogeneous P(VDF-TrFE) / LiCl mixed solution without precipitate.
[0062] Step 3: Mold system-assisted coating 3.1 Mold System Assembly: A conical mold 5 made of polytetrafluoroethylene (PTFE) with both solvent resistance and high temperature resistance is prepared using 3D printing technology. The conical inner diameter of the mold 5 is 0.6 mm, which matches the 400 μm copper wire to ensure uniform coating thickness. The mold is elastically suspended below the equipment by four highly elastic fiber ropes. The length of the fiber ropes is adjustable, giving the mold ±3° of angular freedom, and realizing automatic centering of the metal core 8.
[0063] 3.2 Positioning of the metal core 8: Tension the copper wire prepared in step 1 between the upper and lower pulleys along the axis of the mold, and adjust the height of the pulleys to make the center of the copper wire precisely aligned with the center of the inner hole of the mold.
[0064] 3.3 Solution Injection and Coating: The mixed solution prepared in step 2 is injected into the mold at a rate of 1 mL / min using a syringe, while the copper wire is controlled to move downwards along the axis at a rate of 40 mm / s. The conical structure of the mold generates an axial scraping force F and a radial pressure Q: the axial force precisely controls the coating thickness, and the radial force induces the directional alignment of P(VDF-TrFE) molecular chains through shear orientation, initially promoting the formation of the β phase; when the copper wire deviates, the radial pressure Q generates a torque τ = Q・ΔR (ΔR is the deviation amount), driving the mold to rotate in real time to restore centering and ensure the coaxiality of the coating (e.g., ...). Figure 2 –3 (as shown in Figure 3).
[0065] Step 4: Crystallization in the coagulation bath Immediately immerse the copper wire coated in step 3 into a 25°C pure water coagulation bath, controlling the residence time to 45 seconds. Upon contact between the high-temperature (60°C) P(VDF-TrFE) / LiCl solution and the low-temperature pure water, the solvent DMF rapidly diffuses into the water, while the solution temperature drops sharply, causing P(VDF-TrFE) to instantly reach a supersaturated state. Rapid crystallization is achieved through dynamic phase separation, forming a dense and uniform P(VDF-TrFE) piezoelectric layer on the copper wire surface. The preferred coagulation bath temperature is 25°C. At 0°C, a porous structure is easily formed; at 40°C, the crystallization rate is too slow, leading to a decrease in coating adhesion. At 25°C, solvent diffusion and crystallization rates reach equilibrium, resulting in optimal β-phase induction effect, piezoelectric performance, and cycle stability.
[0066] Too low a temperature can easily form a porous structure that damages the piezoelectric properties, while too high a temperature will slow down the crystallization rate and cause the coating to peel off easily. In addition, the pure water should be replaced every 2 hours to avoid DMF accumulation that could affect the crystallization effect.
[0067] Step 5: Drying to remove solvent The fibers extracted in step 4 are first blown away with compressed air at a pressure of 0.1–0.2 MPa to remove surface moisture, and then placed in an 80℃ hot air drying oven for 30 minutes to completely remove residual DMF solvent in the piezoelectric layer, obtaining a metal core 8-piezoelectric layer composite structure. A polyvinylidene fluoride-trifluoroethylene copolymer solution is coated on the surface of the metal core 8, and polyvinylidene fluoride-trifluoroethylene crystals are formed through a coagulation bath. After drying, the metal core piezoelectric layer 14 is obtained. The thickness of the metal core piezoelectric layer 14 is controlled to be 120 μm.
[0068] Step 6: External Electrode Fabrication and Packaging 6.1 External Electrode Coating: Environmentally friendly conductive copper paint (Kyoto Copprint, Japan) was selected and sprayed onto the surface of the composite structure using an air spraying method. The spraying pressure was 0.3 MPa, the spraying distance was 18 cm, and the spraying was repeated 3 times. After each spraying, the coating was dried at 60°C for 10 minutes to form a 10 μm thick external electrode layer. The metal core 8 serves as the internal electrode, forming a double-layer electrode structure with the external electrode to achieve efficient extraction of piezoelectric charge.
[0069] 6.2 Encapsulation: After the outer electrode is sprayed, the fiber is inserted into the EPDM heat shrink tubing (the inner diameter matches the outer diameter of the fiber). The tubing is heated for 5 minutes at 80°C to make the heat shrink tubing tightly wrap the fiber, which significantly improves the wear resistance and anti-interference ability of the fiber, and finally produces metal core piezoelectric fiber 15 (MPF).
[0070] Step 7: Test Results 7.1 Global Perception Uniformity Test To verify the sensing consistency of the MPF across the entire area, a high-precision dynamic force testing platform (equipped with a VK102 charge amplifier and a USB3210 data acquisition card) was used to conduct a full-area sensing test. A single MPF with a length of 200mm was selected, with one end fixed to the fixed platform 19 and the other end fixed to a suspended 500g weight 18. The weight 18 provided a constant preload of approximately 5N to the MPF. A test point was marked every 20mm along its axial direction, for a total of 10 test points. The pressure test probe 16 applied a constant load of 5N to each test point in a cyclic manner (each test point was repeatedly loaded 10 times). The piezoelectric output voltage at each point was recorded synchronously by the piezoelectric signal data acquisition card 17. The pressure accuracy of each load application was strictly controlled (error ≤ ±0.05N) to ensure the consistency of the test conditions.
[0071] Test results show that under the same 10N load, the maximum piezoelectric output voltage at the 10 test points is 1.40V, the minimum is 1.29V, and the maximum deviation of the output voltage at each point is ≤0.11V. This result confirms that the MPF prepared by the mold-assisted coating process exhibits excellent uniformity in piezoelectric layer thickness, with no local performance differences. This enables full-range, uniform sensing of the monitoring area, avoiding monitoring blind spots or data deviations caused by local performance fluctuations. (See [link to relevant documentation]). Figure 6 As shown on the right side (1).
[0072] 7.2 Cyclic Fatigue Testing To assess the long-term durability of the MPF (polypropylene fiber reinforced polymer) unit, a high-precision dynamic force testing platform (equipped with a VK102 charge amplifier and a USB3210 data acquisition card) was used to conduct cyclic fatigue testing. A single 200mm long MPF unit was selected, with one end fixed to the platform 19 and the other end fixed to a suspended 500g weight 18. The weight 18 provided a constant preload of approximately 5N to the MPF. During the test, the pressure test probe 16 continuously applied a 10N cyclic load to the MPF at a constant frequency of 1Hz, accumulating 500 cycles to simulate the long-term dynamic stress conditions it might experience in practical applications. The final results were synchronously recorded via the piezoelectric signal data acquisition card 17.
[0073] Test results show that the piezoelectric output voltage of MPF under an initial load of 10N is 1.42V; after 500 cycles of loading, the output voltage drops to 1.38V, with a voltage change of only 0.04V and a fluctuation amplitude of only 2.8%. Throughout the entire test cycle, the output voltage waveform maintains a stable sinusoidal characteristic without significant attenuation, signal abrupt changes, or waveform distortion. This result demonstrates that MPF possesses excellent fatigue resistance. The tight bonding between its piezoelectric layer and the metal core 8, along with the high crystallinity of P(VDF-TrFE), effectively resists structural damage under long-term cyclic stress, meeting the requirements of long-term operation in applications such as intelligent sensing and mechanical monitoring. (See [link to relevant documentation]). Figure 6 As shown on the right side (2).
[0074] Example 2 Similar to Example 1, except that the mass fraction of P (VDF-TrFE) in step (2) is 12 wt%. At this point, the solution viscosity and cohesion are at a low level. The low viscosity leads to unstable solution coverage and breakage during spinning, forming large and irregular droplets. See [link to relevant documentation]. Figure 7 As shown in (1).
[0075] Example 3 Similar to Example 1, except that the mass fraction of P (VDF-TrFE) in step (2) is 14 wt%. At this point, the solution viscosity and cohesion remain low, and while the droplet size is reduced, structural irregularities are still retained. See [link to relevant documentation]. Figure 7 As shown in (2).
[0076] Example 4 Similar to Example 1, except that the mass fraction of P (VDF-TrFE) in step (2) is 18 wt%. The increase in nonlinear viscosity leads to shear thinning during extrusion, which inhibits the formation of large-scale beads but exacerbates the formation of small-crystal aggregates. See [link to relevant documentation]. Figure 7 As shown in (4).
[0077] Example 5 Same as Example 1, except that step (2) uses a wet dip-coating process without LiCl addition. Test results show that the β phase content is 48%, while the β phase content in Comparative Example 1 is 92%, showing a significant difference. See [link to relevant documentation]. Figure 8 The comparison image on the right side of the middle section.
[0078] The piezoelectric output voltage under 10N loads for 10 consecutive cycles is 0.51±0.05V, while the piezoelectric output voltage under 10N loads for 10 consecutive cycles in Comparative Example 1 is 1.62±0.05V, showing a certain difference. (See [link]). Figure 9 Comparison curves of the output voltage of the piezoelectric layer on the left and right sides.
[0079] Example 6 Same as Example 1, except that the mass fraction of LiCl in step (2) is 5 wt%. Test results show that the β phase content is 85% (see Example 1). Figure 10 (See the content on the left side). In comparison, the β phase content in Example 1 was 92%, showing a certain difference.
[0080] The average piezoelectric output under 10 consecutive 10N loads is 0.98±0.05V (see [reference]). Figure 10 (Comparison of piezoelectric output voltage curves on the right) In Comparative Example 1, the piezoelectric output voltage under 10N loads for 10 consecutive cycles is 1.47±0.05V, showing a certain difference.
[0081] For the content of LiCl with a mass fraction of 7wt% in step (2) and the voltage curve, please refer to [reference needed]. Figure 10 The comparison chart of the content on the left and the piezoelectric output voltage curve on the right is not described in detail here.
[0082] Example 7 Similar to Example 1, except that the mass fraction of LiCl in step (2) is 9 wt%. Test results show that the β phase content is 94% (e.g., Figure 11 (See left-side β-phase content). In Comparative Example 1, the β-phase content is 92%, indicating a certain increase in β-phase content. (See also...) Figure 11 However, during the dissolution process, LiCl agglomerates due to excessively high concentration, resulting in defects in the piezoelectric layer structure.
[0083] The average piezoelectric output under 10 consecutive 10N loads is 1.42±0.05V (e.g. Figure 11 (Comparison of piezoelectric output voltage curves on the right) In Comparative Example 1, the piezoelectric output voltage under 10N loads for 10 consecutive cycles is 1.47±0.05V, showing a certain difference.
[0084] Comparative Example 1 Conventional electrospinning methods are used, but these methods suffer from drawbacks such as extremely low production efficiency and the inability to achieve continuous production (see Table 1). This invention, through a mold-assisted wet process and the synergistic effect of LiCl, exhibits significant advantages in β-phase content, production efficiency, and structural integration, demonstrating outstanding technological progress.
[0085] Comparative Example 2 Conventional melt coating methods are used, but these methods suffer from poor coating uniformity and interfacial adhesion due to the degradation of the piezoelectric phase structure caused by high temperatures, resulting in a significantly lower β-phase induction efficiency compared to this invention (see Table 1). This invention, through a low-temperature wet process and a LiCl induction system, effectively overcomes the inherent defects of the melt method, demonstrating significant technical superiority.
[0086] Comparative Example 3 Conventional solution coating methods are used, but these methods lack the precise thickness control and centering effect of molds, making it impossible to achieve shear orientation-induced β-phase. This results in coating uniformity and preparation efficiency that are significantly inferior to those of this invention (see Table 1). This invention effectively solves the core defects of this conventional method through mold assistance and synergistic control of the coagulation bath, demonstrating significant technical advantages.
[0087] Table 1 Test results of traditional preparation methods
[0088] The above description is merely a preferred embodiment of the present invention. However, the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention should be covered within the scope of protection of the present invention.
Claims
1. A mold system for preparing metal-core piezoelectric fibers, characterized in that, include: A conical mold with a through conical inner hole for the metal core substrate to pass through and be coated with a piezoelectric material solution; The elastic suspension centering system is connected at one end to the conical mold and at the other end to the fixing device, giving the mold a preset angular degree of freedom to achieve dynamic centering of the metal core substrate.
2. The mold system for preparing metal-core piezoelectric fibers according to claim 1, characterized in that, The preset angle is ±3°.
3. A mold system for preparing metal-core piezoelectric fibers according to claim 1 or 2, characterized in that, The elastic suspension centering system adjusts the tension of the elastic fiber rope to generate torque when the conical mold shifts on the metal core base, driving the mold to rotate and restore centering.
4. An apparatus for preparing metal-core piezoelectric fibers, characterized in that, The mold system comprising any one of claims 1-3, and: A metal core conveying mechanism for conveying a metal core substrate through the conical inner hole; A solution supply mechanism for injecting a piezoelectric material solution into the conical inner hole; A coagulation bath mechanism, located downstream of the mold system, is used to receive the coated metal core substrate and perform crystallization treatment.
5. A method for preparing metal-core piezoelectric fibers based on the apparatus for preparing metal-core piezoelectric fibers according to claim 4, characterized in that, Includes the following steps: Step (1) Metal core substrate pretreatment: Select pure metal wire as substrate, clean and dry it for later use; Step (2), Preparation of mixed solution: Dissolve P(VDF-TrFE) polymer and β phase inducer in organic solvent to form a homogeneous P(VDF-TrFE) / β phase inducer mixed solution; Step (3), mold-assisted coating: the metal core substrate is conveyed through the conical inner hole by the metal core conveying mechanism, and the solution supply mechanism injects the P(VDF-TrFE) / β phase inducer mixed solution obtained in step (2) into the conical inner hole to coat the surface of the metal core substrate. During the coating process, the centering is adjusted in real time by the torque generated by the radial pressure, and the shear force generated by the conical structure is used to induce the orientation of the P(VDF-TrFE) molecular chain. Step (4), solidification bath crystallization: The coated metal core substrate is immersed in the solidification bath mechanism, and P(VDF-TrFE) crystallizes to form a dense piezoelectric layer through dynamic phase separation; Step (5), Drying and post-treatment: Remove the residual organic solvent in the piezoelectric layer, dry it and then prepare the outer electrode and encapsulate it to obtain the metal core piezoelectric fiber.
6. The method according to claim 5, characterized in that, In step (2), the molar ratio of VDF to TrFE in the P(VDF-TrFE) polymer is 80:
20.
7. The method according to claim 5, characterized in that, In step (2), the β-phase inducer is LiCl.
8. The method according to claim 5, characterized in that, In step (2), the mass fraction of P(VDF-TrFE) polymer is 12~18wt% and the mass fraction of β phase inducer is 5~9wt%.
9. The method according to claim 5, characterized in that, In step (4), the crystallization temperature of the coagulation bath is preferably 25°C.
10. The method according to any one of claims 5-9, characterized in that, In step (5), after drying, conductive copper paint is sprayed onto the surface of the piezoelectric layer using an air spraying method to form an outer electrode layer, thus constructing an integrated coaxial structure of "metal-piezoelectric layer-electrode-encapsulation" with a metal core as the inner electrode, conductive copper paint as the outer electrode, and an outer layer encapsulated by EPDM heat shrink tubing.